Comparison between disintegrated and fermented sewage sludge for production of a carbon source suitable for biological nutrient removal - Soares, Ana; Kampas, Pantelis; Maillard, Sarah; Wood, Elizabeth; Brigg, Jon; Tillotson, Martin; Parsons, Simon A.; Cartmell, Elise (Elsevier Science B.V., Amsterdam., 2010)
There is a need to investigate processes that enable sludge re-use while enhancing sewage treatment efficiency. Mechanically disintegrated thickened surplus activated sludge (SAS) and fermented primary sludge were compared for their capacity to produce a carbon source suitable for BNR by completing nutrient removal predictive tests. Mechanically disintegration of SAS using a deflaker enhanced volatile fatty acids (VFAs) content from 92 to 374 mg l−1 (4.1-fold increase). In comparison, primary sludge fermentation increased the VFAs content from 3.5 g l−1 to a final concentration of 8.7 g l−1 (2.5-fold increase). The carbon source obtained from disintegration and fermentation treatments improved phosphate (PO4-P) release and denitrification by up to 0.04 mg NO3-N g−1 VSS min−1 and 0.031 mg PO4-P g−1 VSS min−1, respectively, in comparison to acetate (0.023 mg NO3-N g−1 VSS min−1and 0.010 mg PO4-P g−1 VSS min−1). Overall, both types of sludge were suitable for BNR but disintegrated SAS displayed lower carbon to nutrient ratios of 8 for SCOD:PO4-P and 9 for SCOD:NO3-N. On the other hand, SAS increased the concentration of PO4-P in the settled sewage by a further 0.97 g PO4-P kg−1 SCOD indicating its potential negative impact towards nutrient recyc
Keywords: Denitrification; Mechanical disintegration; Phosphorus release; Primary sludge; Surplus activated sludge